ANALYSIS OF PUBLIC POLICY IMPLEMENTATION ON BUREAUCRACY TRANSFORMATION POST COVID-19 PANDEMIC IN GARUT DISTRICT - Rina Kurniawati (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
As part of the transformation of public services, public service providers can be an instrument to maintain and improve the quality of public services during the Covid-19 pandemic. The government bureaucracy has responded to the changes brought about by this pandemic with various forms of action. The public interest in submitting public service complaints has an increasing trend during the Covid-19 pandemic. The implementation of public services in accordance with the provisions of laws and regulations must carry out legal protection and legal certainty for the general public. The research method used in this article is a qualitative descriptive method, with the type of library research using library data collection methods, reading, and taking notes and processing research materials. The results of the study show the importance of bureaucratic transformation with a dynamic bureaucratic structure and culture as well as the ability to keep up with social changes that occur on the basis of providing maximum public services, especially considering the economic potential of Garut Regency which can be a source of foreign exchange for the country, community especially in Garut Regency. The shift in the public service bureaucracy is expected to encourage economic growth in Garut Regency.